Help-seeking for moderate to severe perinatal depression in Nigeria: Implications for a cultural-ecosocial approach to global mental health - Ademola Adeponle; Danielle Groleau; Oye Gureje; Laurence J. Kirmayer (Elsevier, 2023)
Perinatal depression is a major public health problem that is under-treated in low- and middle-income countries, with negative community attitudes often cited as a major barrier to help-seeking and treatment. In this paper, we investigate help-seeking for perinatal depression, some of whom may have experienced psychosis in the context of perinatal depression, and its cultural shaping in Nigeria. Our approach was informed by cultural constructivist and critical anthropological perspectives to situate perinatal depression in ecosocial context with systematic attention to the social-structural determinants. Help-seeking was controlled by caregivers, but patients and caregivers differed in their definitions of illness onset: caregivers focused on violation of norms for maternal behavior, whereas patients focused on somatic and psychological distress. Help-seeking entailed use of two different reasoning approaches. The default approach was ad-hoc and contingency-based, depending on: 1) the kinds of help immediately available and the fit with experiential knowledge; 2) the meanings of the patient's problem as negotiated in social interactions; 3) concerns about stigma that led to secrecy in seeking help; and 4) the perceived degree of immediate risk to safety. The second approach involved more explicit deliberation and took over in situations of uncertainty including: 1) worsening or unremitting illness despite treatment; 2) harm from treatment; and 3) perceived inadequacy of a treatment to bring about healing. Avoiding mental illness stigmatization was seen as dependent on limiting public awareness of the individual's affliction. The meanings of illness were locally informed and negotiated in ongoing social interactions and practices of social recognition and status negotiation that legitimated illness and influenced help-seeking. Clarifying the social context of mental health problems and identifying cultural and structural risk and protective factors can inform the design of health care systems to improve access to care and the development of culturally appropriate and effective intervention programmes.